2008
DOI: 10.1002/wcm.654
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and problems of wireless communication for underwater sensor networks

Abstract: SummaryThis paper reviews the physical fundamentals and engineering implementations for efficient information exchange via wireless communication using physical waves as the carrier among nodes in an underwater sensor network (UWSN). The physical waves under discussion include sound, radio, and light. We first present the fundamental physics of different waves; then we discuss and compare the pros and cons for adopting different communication carriers (acoustic, radio, and optical) based on the fundamental fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(112 citation statements)
references
References 64 publications
0
109
0
3
Order By: Relevance
“…The major advantage compared to RF communications is the possibility of keeping the same conditions underwater without considerable losses. The disadvantage of optical is scattering and interference with ambiance light that can alter communications [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The major advantage compared to RF communications is the possibility of keeping the same conditions underwater without considerable losses. The disadvantage of optical is scattering and interference with ambiance light that can alter communications [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, at ranges of less than 100 m the data transmission rates of these systems in shallow littoral waters are ∼10 kb/s. Experimental tests have shown that an alternative feasible solution is optical communication especially in blue/green light wavelengths, even if limited to short distances (up to 100 m) (Lanbo et al, 2008). Compared to acoustic communication it offers a practical choice for high-bandwidth communication and it propagates faster in the water (2.255 x 10 8 ).…”
Section: Underwater Wireless Communication: Physical Aspectsmentioning
confidence: 99%
“…A comparison between different wireless underwater technologies for underwater communication is illustrated in Table 1. et al, 2001) (Akyildiz et al, 2005) (Lanbo et al, 2008). The main limitations due to acoustic communication, which will be described can be summarized as follows:…”
Section: Underwater Wireless Communication: Physical Aspectsmentioning
confidence: 99%
“…This can be seen in both civil and military operations the world over and are applied in transmitting voice, data and video to various location [2,3,4]. In the bid to improve on the coverage, capacity and quality of service for radio wave communication systems, experts have found that the propagation of radio signals through the atmosphere is greatly influenced by the effective earth radius factor k [5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%